Mutations in the lipase‐H gene causing autosomal recessive hypotrichosis and woolly hair. (13th March 2014) - Mehmood, Sabba; Jan, Abid; Muhammad, Dost; Ahmad, Farooq; Mir, Hina; Younus, Muhammad; Ali, Ghazanfar; Ayub, Muhammad; Ansar, Muhammad; Ahmad, Wasim
Abstract Hypotrichosis is characterised by sparse scalp hair, sparse to absent eyebrows and eyelashes, or absence of hair from other parts of the body. In few cases, the condition is associated with tightly curled woolly scalp hair. The present study searched for disease‐causing sequence variants in the genes in four Pakistani lineal consanguineous families exhibiting features of hypotrichosis or woolly hair. A haplotype analysis established links in all four families to the LIPH gene located on chromosome 3q27.2. Subsequently, sequencing LIPH identified a novel non‐sense mutation (c.328C>T; p.Arg110*) in one and a previously reported 2‐bp deletion mutation (c.659_660delTA, p.Ile220ArgfsX29) in three other families.